Labelisasi dan Pemasaran Produk Industri Rumah Tangga Minyak Tandusan dalam Upaya Peningkatan Kesejahteraan Ibu-Ibu PKK Banjar Dinas Apit Yeh Kaja, Desa Manggis Kabupaten Karangasem - Putu Eka Purnamaningsih; Kadek Wiwin Dwi Wismayanti; I Ketut Winaya; Ni Wayan Ari Sudiartini (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Banjar Dinas Apit Yeh kaja where part of the population depends on plantations, especially gardening with coconut, bananas and leaves. The economic downturn during this pandemic has forced mothers to be more creative and innovate by utilizing the plantation products they have, namely by making barren oil made from processed coconuts. Tandusan Oil or Balinese Oil is mostly produced by Home Industries in Bali in general and in particular in Banjar Dinas Apit Yeh Kaja, Manggis Village, Karangasem Regency. The PKK women's group is a forum for improving welfare through the production of barren oil by labeling and marketing the products of the home industry of this wasteful oil to a wider market share. With this Community Service Program, PKK Apit Yeh Village women can increase productivity in producing barren oil with attractive packaging and develop marketing by attracting potential consumers through Digital Marketing.